Surviving in the dark: The mortality effects of reducing rolling blackouts - Joshua Budlender (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
South Africa frequently experiences rolling blackouts ('load shedding') due to shortfalls in electricity generation. This is a common problem across the developing world, and yet the developmental impacts of insufficient and unstable electricity supply, and the benefits of mitigating this, are poorly understood. I use the introduction of a unique load shedding reduction policy in parts of South Africa's second-largest city, Cape Town, to investigate the mortality effects of load shedding and its mitigation. To identify these effects, I use a stacked synthetic control design that leverages the episodic nature of load shedding between 2014 and 2019. While the estimates are imprecise, I find robust evidence that the mitigation policy statistically significantly reduces mortality in Cape Town relative to other parts of South Africa experiencing unmitigated load shedding. The incomplete geographic coverage of the mitigation policy entrenches existing inequalities in the city.
Keywords: I15; O13; Q48; C23; 330; rolling blackouts; mortality; load shedding; synthetic control; Cape Town; South Africa